THE EFFECTIVENESS OF USING PERSONAL VOCABULARY NOTES (PVN) TO TEACH ENGLISH VOCABULARY - Yulianti, Lisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research applied pre-experimental method with one group of pre-test and post-test design. The purpose of this research was to find out whether or not using Personal Vocabulary Notes (PVN) is effective to teach English vocabulary. The population of this research was Year-8 students of SMP Negeri 1 Sambas. The sample was 33 students of class VIII E. The technique to collect the data was measurement technique. The form of the test was multiple choice and short answer. The result of studentsâ€™ mean score of post-test is 72.12 higher than their mean score of pre-test which is 57.27. The effect size of the treatment is 1.89, which is categorized as effective. The effect size of the treatment is higher than the highest category of effect size that is 1.00 (1.89 > 1.00). The research finding shows it is effective to teach English vocabulary using Personal Vocabulary Notes (PVN) to Year-8 students of â€œSMP Negeri 1 Sambasâ€ in Academic Year 2015/2016.Â Keywords: Personal Vocabulary Notes (PVN), teaching, vocabulary